Not Content with Content: Ruptures in Media Discourse and Production? - Salman, Sarah Jean (AoIR Selected Papers of Internet Research, 2026)
Cultural producers of what one might consider more traditional media have denounced content (shorthand for digital, social media, or online objects) as an object as a far cry from creative output, and the term as an assault on art. Writers, directors, musicians, actors, and even stand-up comedians have not only disparaged content, but also those that produce it. As content is increasingly used to refer not just to media that circulates online but to the products of traditional cultural industries offline too, these producers have disparaged the use of the term and content itself as an assault on their outputs. Through critical discourse analysis of statements and conversations from filmmakers, actors, writers, musicians, and stand-up comedians, I examine how traditional cultural producers negotiate the term content’s application in and encroachment on their fields. I argue that discourse about content is not representative of a sea change in art’s integrity as much as it is a term that creators use to express anxieties about the devaluation of their work in response to changing political economic arrangements that the internet has catalyzed. As their work becomes increasingly accessible to larger audiences via digitization, cultural creators worry that their work is becoming less precious, sanctified, and more easily consumed and discarded, i.e., that their work could become content.